Logging intensity reshapes insect biodiversity in pine wilt disease forests: a multi-trophic assessment from Jiangxi, China - Wang, Yiming; Liu, Xiaohua; Jin, Mingxia; Xie, Gu-ai; Li, Longjun; Yu, Ailin (Frontiers in Forests and Global Change, 2025)
IntroductionPine wilt disease (PWD), caused by Bursaphelenchus xylophilus, has led to widespread logging interventions in subtropical China, especially clearcutting, yet the ecological consequences for insect communities remain poorly understood. Insects play critical roles in ecosystem functioning, making it essential to quantify how different logging strategies shape their diversity, community composition, and functional guilds.MethodsWe established 48 stratified plots across four PWD-affected counties in Jiangxi Province to compare unlogged controls (UC), selection cutting (SC), and clearcutting (CC) treatments. Insect diversity was evaluated using Shannon and Simpson indices, while community structure was analyzed with PERMANOVA and NMDS ordinations. Indicator species were identified via IndVal analysis. Functional guild dynamics were measured across trophic groups, and structural equation modeling (SEM) was used to assess vegetation cover and litter thickness as mediators of diversity responses.ResultsClearcutting caused significant declines in insect diversity (Shannon index: UC 3.63 ± 0.02 vs. CC 3.14 ± 0.18; F = 19.17, p = 0.00057; Simpson index: UC 0.960 vs. CC 0.919). PERMANOVA attributed 60.7–89.5% of variation in insect community structure to logging treatment (p < 0.05), with NMDS ordinations showing distinct clustering: CC sites were dominated by disturbance-tolerant taxa (e.g., Cicindelidae, IndVal = 0.94), while UC sites harboured specialists (e.g., Libellulidae, IndVal = 0.95). Functional guild analysis revealed strong reductions in predators (−63.7%) and parasitoids (p < 0.001) under CC, whereas decomposers were relatively resilient. SEM demonstrated that vegetation cover (β = 0.69, p < 0.001) and litter thickness (β = 0.25, p = 0.041) acted as key mediators, with logging intensity indirectly depressing insect diversity via microhabitat degradation (model R2 = 0.81).Discussion and conclusionOur findings show that intensive clearcutting exacerbates biodiversity loss and trophic collapse in insect communities of PWD-affected pine forests, largely through reductions in vegetation structure and litter. In contrast, lighter interventions such as selection cutting supported greater ecological resilience. To balance disease control with biodiversity conservation, retention forestry practices maintaining ≥30% canopy cover and 20–30 m3/ha deadwood are recommended to buffer microhabitats and sustain insect community functioning.